2000
DOI: 10.1046/j.1460-9568.2000.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal expression of c‐Fos and Zif268 in the rat basal ganglia: immunohistochemical characterization of striatal Zif268‐positive neurons

Abstract: Basal expression of the protein products of the inducible immediate early genes (IEGs), c-Fos and Zif268, was investigated in five regions of the rat basal ganglia using immunohistochemistry. In particular, high basal levels of Zif268 but very low levels of c-Fos were seen in the caudate-putamen (CPu). Double immunostaining revealed that many of the constitutively expressed Zif268-positive neurons were GABAergic but very few were cholinergic or neuronal nitric oxide synthase (nNOS)-positive, and some of the Zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Constitutive levels of Zif268 were seen in the striatum, where very low levels of Fos were observed, consistent with that seen in previous studies (Ishida et al, 2000;MacGibbon et al, 1995). Constitutively expressed IEGs may perhaps be involved in control- i.p.)…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Constitutive levels of Zif268 were seen in the striatum, where very low levels of Fos were observed, consistent with that seen in previous studies (Ishida et al, 2000;MacGibbon et al, 1995). Constitutively expressed IEGs may perhaps be involved in control- i.p.)…”
Section: Discussionsupporting
confidence: 90%
“…(Seyfert et al, 1990). A previous report suggested that Zif268 may play a role in spontaneously maintaining the inhibitory output of GABAergic neurons in the striatum (Ishida et al, 2000). Based on the results described previously (Ishida et al, 1996;Schmidt et al, 1983), it appears that an almost complete loss of the DA content is achieved in the denervated striatum in the 6-OHDA-treated rats in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Different types of interneurons and pyramidal cells have been detected in the sensory cortex and may be differentially recruited by emotionally-laden experiences. zif268 expression has been detected in both glutamatergic and GABAergic cells in several brain structures (Ishida et al 2000). Therefore, further studies are needed to better characterize the neuronal populations engaged in the different layers during fearand/or appetitive memory processes.…”
Section: Factors Determining Layer-and Regional-differences Between Gmentioning
confidence: 99%